Numerical Performance Analyses of Different Airfoils for Use in Wind Turbines - Duz, Hasan; Yildiz, Serkan (International Journal of Renewable Energy Development, 2018)
This study numerically investigated different types of high-performance airfoils in order to increase the efficiency of wind turbines. Performances of five airfoil types were numerically simulated at different attack angles (0 Â° <Î± <20 Â°) and at different wind speeds (4, 8, 16 and 32 m/s). Numerical analysis shows that all airfoils achieve the highest performance at attack angles between 4o and 7o. Results also show that the performance of all airfoils increases in direct proportion to increase in wind speed with a low gradient. A new hybrid airfoil was generated by combining lower and upper surface coordinates of two high-performance airfoils which achieved the better results in pressure distribution. Numerical analysis shows that the hybrid airfoil profile performs up to 6% better than other profiles at attack angles between 4o and 7o while it follows the maximum performance curves closely at other attack anglesArticle History: Received January 16th 2018; Received in revised form June 5th 2018; Accepted June 15th 2018; Available onlineHow to Cite This Article: Duz, H and Yildiz, S. (2018) Numerical Performance Analyses of Different Airfoils for Use in Wind Turbines. Int. Journal of Renewable Energy Development, 7(2), 151-157.https://doi.org/10.14710/ijred.7.2.151-157Â